2019
DOI: 10.3168/jds.2018-15865
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory properties of milk supplemented with lactase microcapsules coated with enteric coating materials

Abstract: In this paper, we report the physicochemical and sensory properties of milk supplemented with a powder of microencapsulated lactase. The core material was lactase (β-galactosidase), the primary coating material was medium-chain triglyceride (MCT), and the secondary (enteric) coating material was either hydroxypropyl methylcellulose phthalate (HPMCP) or shellac, comparing both against market milk as a control. The physicochemical properties of both types of microcapsules were analyzed, including the particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…[47] The shellac-coated microcapsules had a negative zeta potential of −87.10 mV at pH 7.0, partly because of the negative charge of carboxylic acid groups (-COO − ). [25] It has also been reported that galacturonic acid residues of polysaccharide from the medicine plants, such as…”
Section: Blood Compatibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[47] The shellac-coated microcapsules had a negative zeta potential of −87.10 mV at pH 7.0, partly because of the negative charge of carboxylic acid groups (-COO − ). [25] It has also been reported that galacturonic acid residues of polysaccharide from the medicine plants, such as…”
Section: Blood Compatibilitymentioning
confidence: 99%
“…Thus, it is plausible to suggest that the release of shellac from the coatings into the culture medium is the primary reason for the inhibition of viability and proliferation of ECs observed for the SH25 and SH50 samples. The carboxyl ions (COO) [25][26][27] released from the coatings, as indicated by the reduced pH values (Figure 3c), can be the underlying mechanism behind the inhibition of cell viability and proliferation of shellac coatings. Such ability of shellac in inhibiting the growth of ECs can provide an unprecedented opportunity to modify the surfaces of inferior vena cava filters for inhibiting the adhesion of cells and improving the retrievable rate of inferior vena cava filters.…”
Section: Viability and Proliferation Of Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microencapsulation has proposed a solution to this problem by incorporating the enzyme into the same dairy product. β-D-galactosidase was microencapsulated in hydroxypropyl methylcellulose phthalate, which was added to milk (approximately 0.148 g of enzyme), controlling its release, preventing its hydrolysis, and retaining 81.18% of the enzyme after 12 days in refrigeration [ 75 ]; the formulation of microemulsions in caseinates and sodium lecithin has also been proposed to encapsulate lactase and control its release and degree of hydrolysis in products such as skim and full-fat milk [ 75 , 76 ].…”
Section: Microcapsules In Functional Foodsmentioning
confidence: 99%
“…Microencapsulation of indomethacin, acetaminophen, aspirin, insulin, and other drugs has been studied in regard to sustained-release properties and stabilization in the presence of oxygen characteristics (Roshan et al, 2016; Liu et al, 2004; Mutaliyeva et al, 2017). Similarly, microencapsulation of vitamins, flavors, probiotics, and enzymes has been studied for use in food processing (Ahn et al, 2019; Liu et al, 2001; Shah and Ravula, 2000; Uddin et al., 2001). Microencapsulation of flavor could protect the flavor components from unwanted chemical changes and may retain the flavor during manufacture or storage (Shahidi and Han, 1993).…”
Section: Introductionmentioning
confidence: 99%